Variation of Photosynthesis, Fatty Acid Composition, ATPase and Acid Phosphatase Activities, and Anatomical Structure of Two Tea (Camellia sinensis (L.) O. Kuntze) Cultivars in Response to Fluoride - L. X. Wang; J. H. Tang; B. Xiao; Y. J. Yang; J. Liu (The Scientific World Journal)
The changes of photosynthetic parameters, water use efficiency (WUE), fatty acid composition, chlorophyll (Chl) content, malondialdehyde (MDA) content, ATPase and acid phosphatase activities, fluoride (F) content, and leaf anatomical structure of two tea cultivars, “Pingyangtezao” (PY) and “Fudingdabai” (FD), after F treatments were investigated. The results show that net photosynthetic rate (), stomatal conductance (), and transpiration rate (E) significantly decreased in both cultivars after 0.3 mM F treatment, but FD had higher , , and WUE and lower E than PY. Chl content in PY significantly decreased after 0.2 and 0.3 mM F treatments, while no significant changes were observed in FD. The proportions of shorter chain and saturated fatty acids increased and those of longer chain and unsaturated fatty acids decreased in both cultivars under F treatments. The contents of MDA increased after F treatments but were higher in PY than in FD. In addition, F treatments decreased the activities of ATPase and acid phosphatase and increased F content in both cultivars; however, compared with PY, FD showed higher enzymatic activities and lower F content in roots and leaves. Leaf anatomical structure in FD indicated that cells in leaf midrib region were less injured by F than in PY.